Integrative nursing interventions: knowledge, attitudes and practice in home nursing services in Germany—a quantitative and qualitative online survey - Stolz, Regina; Klocke, Carina; Mahler, Cornelia; Valentini, Jan; Joos, Stefanie (Frontiers in Medicine, 2024)
Introduction: Integrative nursing interventions (INI) play a significant role in healthcare, particularly in the prevention and treatment of chronic diseases. Integrating evidence-based INI into healthcare aligns with global initiatives such as the WHO's Decade of Healthy Aging 2020-2030. Many INI are low-threshold practices, empowering patients to independently manage health. However, the extent to which INI are used by home-care nursing-services (HNS) remains largely unknown. This study aims to explore the field of INI in German HNS regarding nurses' use of INI as well as attitudes, subjective knowledge, and information needs on the subject. Methods: A cross-sectional anonymous online survey with 29 Likert scale items and two openended questions was conducted between April 2023 and July 2023. The survey targeted nurse managers of HNS in Baden-Württemberg, Germany. Descriptive analysis was performed for quantitative data, while content analysis according to Kuckartz was applied to analyze open-ended text responses. Results: In total, n=68 out of n=1331 HNS took part in the survey yielding a response rate of 5.1%. Their overall attitude towards INI was clearly positive (10-point Likert scale M ± SD: 8.37 ± 2.22). The average self-assessed knowledge level about INI was moderate (M ± SD: 5.39 ± 2.76). Almost half of the participants (45.6%) declared to incorporate INI in patient care. Most participants (84.2%) lacked employees with additional qualifications in INI. The INI used most were medicinal herbal teas (61%), compresses (57%), and aromatherapy (48%). Acupressure showed the greatest disparity between actual use in participating HNS (4.3%) and interest in further education (61%). The most common symptoms for which INI are used are pain, respiratory problems, anxiety, and palliative care. The main challenges reported for the use of INI in HNS are financial aspects, qualification and limited resources (staff and time).Discussion: This exploratory study provides the first insights into nurses' attitudes, self-assessed knowledge, and utilization of INI in German HNS. Overall response rate was low (5.1 %), therefore, the results should be interpreted with caution. Urgent action is needed to address financial aspects and further education on INI, to promote integration of INI in HNS to the best possible extent.